PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, KOMUNIKASI DAN PROFESIONALISME TERHADAP KESIAPAN PEMERINTAH DAERAH DALAM PENERAPAN PERMENDAGRI NOMOR 77 TAHUN 2020 DENGAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERASI - Sri Wahyuni Zanra (CV. Denasya Smart Publisher, 2024)
This study aims to determine the effect of human resource competence, communication, and professionalism on the readiness of local governments to implement Permendagri Number 77 of 2020 moderated by information technology. The population in this study were all Regional Work Units within the Pekanbaru City Government as many as 33 SKPD. In this study, researchers used the Saturated Sampling method with a total of 165 respondents (each SKPD was represented by 5 respondents). Data analysis using SEM-PLS with SmartPLS software. The results of the study concluded that the competence of human resources, communication and information technology influences the readiness of local governments in implementing Minister of Home Affairs Regulation Number 77 of 2020 while the professionalism variable does not affect the readiness of local governments to implement Permendagri Number 77 of 2020. In addition, the information technology variable as the moderating variable is proven to be able to moderate the relationship between human resource competence, communication and professionalism on the readiness of local governments to implement Permendagri Number 77 of 2020